Data Mining Approaches to Predict the Factors that Affect the Agriculture Growth using Stochastic Model - Rajesh, P; Karthikeyan, M (International Journal of Computer Sciences and Engineering, 2025)
In the recent times, there has been an increasing demand for efficient strategies in the data mining in agriculture prediction. Data mining is equipment to predict effectively by stochastic model sensing concept. This paper proposes an efficient factor that affects the agriculture growth using different data like rainfall, groundwater and temperature by adopting stochastic modeling and data mining approaches. Firstly, the novel model is proposed to predict the factors affecting the growth of agriculture using stochastic model and numerical illustrations are done and the various expected estimation the sternness of the proposed approach.